2017
DOI: 10.1016/j.amjmed.2017.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration Pneumonia in Carbon Monoxide Poisoning Patients with Loss of Consciousness: Prevalence, Outcomes, and Risk Factors

Abstract: The prevalence of aspiration pneumonia was 19.2% in carbon monoxide poisoning patients with loss of consciousness and was associated with poor outcomes. Additionally, altered mental status on emergency department arrival, white blood cell count, and increased exposure duration were independently associated with the development of aspiration pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In addition, Kim et al (2018) stated that increased CO exposure duration was associated with increased risk of acute brain injury occurrence. Also, it was reported that prolonged CO exposure duration and decreased consciousness (low GCS) were associated with increased risk of neurological sequelae (Kitamoto et al, 2016), increased risk of aspiration pneumonia and poor outcome (Sohn et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kim et al (2018) stated that increased CO exposure duration was associated with increased risk of acute brain injury occurrence. Also, it was reported that prolonged CO exposure duration and decreased consciousness (low GCS) were associated with increased risk of neurological sequelae (Kitamoto et al, 2016), increased risk of aspiration pneumonia and poor outcome (Sohn et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…CO intoxications are clinical dose-dependent and the clinical deterioration occurs as the COHb level increases. In severe poisonings, loss of consciousness, chest pain, cardiovascular diseases, delayed neurological sequelae, coma, and death can be seen (18). It has been reported that there is no clear relationship between exposure time and ABI (19).…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted, the mortality rates in CO intoxications have been reported to be between 1-3% (4,18). In a study, it was stated that the frequency of ABI is high in patients with mortality (14).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to CO 2 levels of approximately 50,000 ppm can lead to the failure of the central nervous system (brain and spinal cord), possibly causing death [22]. On the other hand, breathing high levels of CO can lead to death due to tissue hypoxia, as CO can bind to hemoglobin more effectively than oxygen [23].…”
Section: Introductionmentioning
confidence: 99%